2019
DOI: 10.1111/jnc.14705
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐coupled glucose phosphorylation develops after birth to modulate H2O2 release and calcium handling in rat brain

Abstract: The adult brain is a high-glucose and oxygen-dependent organ, with an extremely organized network of cells and large energyconsuming synapses. To reach this level of organization, early stages in development must include an efficient control of cellular events and regulation of intracellular signaling molecules and ions such as hydrogen peroxide (H 2 O 2 ) and calcium (Ca 2+ ), but in cerebral tissue, these mechanisms of regulation are still poorly understood. Hexokinase (HK) is the first enzyme in the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Markers of oxidative stress increase at the onset of adolescence and during adult aging, both in the brain and periphery [124][125][126]. In brain-derived mitochondria, the rate of aerobic respiration increases during early postnatal and adolescent development, reaching adult levels at ~P60 (end of adolescence/onset of adulthood) in rats [127]. Oxidative stress occurs when the reactive oxygen species formed as natural byproducts of aerobic respiration accumulate to deleterious levels and cause damage to DNA, lipids, and other cellular components susceptible to oxidation.…”
Section: Neurobiology During the Age Of Scz Onsetmentioning
confidence: 99%
“…Markers of oxidative stress increase at the onset of adolescence and during adult aging, both in the brain and periphery [124][125][126]. In brain-derived mitochondria, the rate of aerobic respiration increases during early postnatal and adolescent development, reaching adult levels at ~P60 (end of adolescence/onset of adulthood) in rats [127]. Oxidative stress occurs when the reactive oxygen species formed as natural byproducts of aerobic respiration accumulate to deleterious levels and cause damage to DNA, lipids, and other cellular components susceptible to oxidation.…”
Section: Neurobiology During the Age Of Scz Onsetmentioning
confidence: 99%
“…During neurodevelopment and in adult brain cells, ROS have important signaling roles in proliferation, differentiation, and migration (Kennedy, Sandiford, Skerjanc, & Li, 2012;Wilson, Muñoz-Palma, & González-Billault, 2018). In neural cells, most hexokinase is bound to OMM, possibly due to the modulation of ROS generation associated with the activity of mt-HK (da-Silva et al, 2004;de-Souza-Ferreira, Rios-Neto, Martins, & Galina, 2019). Therefore, measuring mt-HK enzymatic activity, particularly in human neural cells, constitutes an interesting strategy to assess mitochondrial function more fully.…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Despite the complexity of mitochondrial calcium dynamics modulation, there are some possible explanations for variations in the functional parameters. It has been recently shown that activation of mitochondrial hexokinase, an enzyme bound to the outer mitochondrial membrane that phosphorylates glucose in a reaction coupled to OXPHOS, increases the uptake of calcium by brain mitochondria (de-Souza-Ferreira et al, 2019), probably due to the modulation of ADP/ATP cycling and of physiological mPTP opening (Jonas et al, 1999). Therefore, if an improvement in the uptake of calcium influx rate is observed in astrocytes or other neural cells in the presence of glucose, it may reveal the stimulation of mt-HK activity or another system that modulates nucleotide cycling.…”
Section: Possible Cause Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mitochondrial ROS and their regulation by mt-HK are important for neurodevelopment [ 28 ]. Our group showed that mt-HK activity linearly increases throughout neurodevelopmental stages [ 29 ], correlating with oxidative metabolism and mitochondrial ROS production, unlike classical antioxidant systems [ 30 ]. This observation suggests that mt-HK may also modulate mitochondrial ROS during brain development.…”
Section: Introductionmentioning
confidence: 99%